Dysbiosis significantly elevates the probability of altered affective function in Alzheimer disease (AD) - Kumar, Harsh; Dhanjal, Daljeet Singh; Dhalaria, Rajni; Kimta, Neetika; Cimler, Richard; Kuča, Kamil (International review of neurobiology, 2025)
Changes in the makeup of gut microbiota are linked to many neuropsychiatric diseases. Although the exact connection between gut dysbiosis and brain dysfunction is not yet fully understood, but recent data suggests that gut dysbiosis may contribute to the development of Alzheimer's disease (AD) by promoting neuroinflammation, insulin resistance, oxidative stress, and amyloid-beta (Aβ) aggregation. Gut dysbiosis in animal models is primarily characterized by an elevated ratio of Firmicutes/Bacteroidetes which may lead to the accumulation of amyloid precursor protein (APP) in the intestine, in the early stages of AD. Probiotics play a significant role in preventing against the symptoms of AD by restoring gut-brain homeostasis. This chapter provides an overview of the gut microbiota and its dysregulation in etiology of AD. Moreover, novel insights into alteration of the composition of gut microbiota as a preventive or therapeutic approach to AD are discussed.
Keywords: Animals; Alzheimerova nemoc; Probiotics; lidé; zvířata; Dysbiosis; střevní mikroflóra; probiotika; Alzheimer Disease; dysbióza; Gastrointestinal Microbiome; Humans